Biological effects of cinnamaldehyde in animal cancer models: a systematic review and meta-analysis - Luo, Dan; Luo, Xu; Xie, Jinghui; Ye, Keying; Wang, Xiangjin; Hu, Xiyue; Liu, Chenhao; Liu, Yi (Frontiers in Pharmacology, 2025)
BackgroundCinnamaldehyde (CA), a naturally occurring aromatic aldehyde from cinnamon bark, has been investigated for its biological activity in laboratory settings. However, its α,β-unsaturated aldehyde structure designates it as a pan-assay interference compound (PAINS), which can produce non-specific effects through chemical reactivity—particularly in vitro—raising concerns about the validity and interpretation of its reported anti-tumor activity.ObjectiveTo systematically review and synthesize existing animal studies that examine the biological effects of CA on tumor growth, while critically evaluating the strength, limitations, and plausibility of the evidence, especially in light of CA’s PAINS-related characteristics.MethodsA systematic literature search was conducted across eight electronic databases to identify relevant animal studies assessing the effects of CA on tumor progression. Study quality was evaluated using the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) risk of bias tool. Quantitative synthesis was performed using Review Manager (RevMan) 5.3. In vitro studies were excluded due to concerns regarding non-specific activity and limited translatability.ResultsSixteen studies encompassing 19 independent experiments and 302 animals were included. Pooled results indicated that CA administration was associated with reductions tumor volume and tumor weight in animal models. However, no improvement in survival was observed, and CA-treated animals showed a modest decrease in body weight. Additionally, reduced expression of proliferating cell nuclear antigen (PCNA), hypoxia-inducible factor (HIF), vascular endothelial growth factor (VEGF), and microvessel density was reported. Despite these findings, the absence of controls for. Non-specific reactivity makes it difficult to distinguish true pharmacological effects from general cytotoxic or chemical stress responses.ConclusionWhile CA has demonstrated anti-tumor effects in animal models, these observations should be interpreted with caution. Its classification as a PAINS compound, coupled with a lack of mechanistic specificity, appropriate controls, and clinical validation, limits the reliability and translational relevance of the existing data. The observed outcomes are more likely reflective of non-specific chemical activity rather than targeted therapeutic action. Future research should prioritize rigorous mechanistic validation, use of non-reactive analogs, and comprehensive toxicity profiling before considering any clinical applicability.